A STUDY OF SOCIAL MEDIA INFLUENCERS’ IMPACT ON CONSUMERS’ PURCHASING INTENTIONS FOR BEAUTY PRODUCTS - Batdelger, Dulguuntsetseg; Ganbold, Munkhbayasgalan (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
Influencer marketing is becoming increasingly prominent in the beauty industry. The research examines the effects of influencers’ personal characteristics (attractiveness, trustworthiness, and expertise) and content characteristics (information quality, creativity, and design quality) on consumer attitudes and purchase intentions toward beauty products. Data were collected from 384 women aged 16 and above in Mongolia who actively use social media and follow beauty social media influencers. A structured questionnaire was distributed via Google Forms, and the data were analyzed using SPSS. Proposed seven hypotheses, and six were supported.